The Concept of Gharar in Purchasing Mobile Legends Virtual Items: A Study of the Clarity of Objects and Transactions - Erlangga Aditia Putra (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
The development of online games such as Mobile Legends has created various transaction models, including the purchase of virtual items, which raises questions regarding its suitability with the principles of Islamic economic law. This study aims to analyze the existence of the element of gharar (uncertainty) in the purchase of Mobile Legends virtual items based on the perspective of fiqh muamalah. The focus of the study includes the clarity of the transaction object (virtual item) and the payment mechanism. The method used is a qualitative approach with normative analysis of fiqh literature, related fatwas, and in-game transaction models. The results show that the purchase of virtual items in Mobile Legends has the potential to contain elements of gharar in the aspects of clarity of benefits, ownership, and continued access to items by users. In addition, the payment system based on digital currency (diamonds) that has no intrinsic value creates ambiguity in the sale and purchase contract. This study recommends improving the transaction mechanism in online games to be more transparent and in accordance with sharia principles, such as explaining the benefits of items in detail and certainty of ownership rights. This study contributes to the development of sharia regulations that are relevant to the digital economy ecosystem.